Relações de poder, fragmentação e gestão do território no semi-árido nordestinho: um outro olhar sobre o Cariri paraibano - Silva, Anieres Barbosa da (2006)
This study aims to analize the Cariri Paraibano territory, as a product of relations of power that were being established along its historic process of territory formation. In this process, the fragmentation and the territory management are fundamental elements to socioterritorial reality comprehension. The theoretical-conceptual basis is based on notions of territory, region, power and territory management, which are articulated to the opinions and empiric confirmations origined from interviews made with several social actions. They also were made photographical records and researches on books, newspapers and magazines, as well on other information sources related to the object of studying. Obtained data confirm the pressuposement on which the relations of dominations and the used methods by the power s owners in the region created a little fruitful political practice and little adequate to the process of active participation of the local population on the territory management, even being on disagreement with the new political-institutional mechanisms, which take to political-administrative more democratic and participative in the country